Governmentality, Religion, and Sustainability: Reinterpreting Marine Tourism Governance in the SDGs Era - Siti Zunariyah; Sri Hilmi Pujihartati; Faline Izza Nisa'u (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This research is in the field of religious, social, and cultural studies, focusing on marine tourism governance from the perspective of governmentality and the interaction between power, spirituality, and sustainability. Papuma Beach in Jember Regency was chosen as the study location because it illustrates the complexity of coastal tourism management, which is fraught with economic interests and formal power, but on the other hand has a strong spiritual value system in the local community. This research aims to identify the forms of power at work in tourism management and understand how religion plays a role in the production of meaning around sustainability and resistance to technocratic development models. The methods used are a critical qualitative approach with participatory observation techniques, in-depth interviews, and documentary studies. The results show that the dominance of the state and market in the management of Papuma tourism creates cultural dislocation and marginalization of local communities. However, the community has developed various forms of symbolic resistance and alternative practices based on religious values and local wisdom. This study contributes to the development of governmentality theory in a local context and expands the discourse on sustainability by integrating maqāṣid al-sharī‘ah and eco-theology as analytical frameworks. In conclusion, equitable tourism development can only be achieved through participatory governance rooted in community values. These findings are important as a basis for formulating contextual, fair, and locally rooted sustainable tourism policies.